Schisandrin B Inhibits Osteoclastogenesis and Protects Against Ovariectomy-Induced Bone Loss - Wang, Jia; Fang, Zhong; Song, Chao; Kang, Honglei; Guo, Qian; Dong, Yimin; Zhang, Ya; Peng, Renpeng; Guan, Hanfeng; Li, Feng (Frontiers in Pharmacology, 2020)
Osteoporosis is a systemic skeletal disease which is highly prevalent worldwide and considered to be associated with excessive bone resorption mediated by osteoclast. Osteoclast differentiation is featured by the activation of inflammation-related pathways and the generation of reactive oxygen species. Schisandrin B is a bioactive compound with strong antiinflammation and antioxidative properties, we thus speculated that Schisandrin B might serve as a potential candidate for osteoporosis. In the present study, we found that the formation and` function of osteoclasts were dramatically suppressed by Schisandrin B. And consistent with the in vitro results, treatment with Schisandrin B attenuated ovariectomy-induced bone loss in mice. Moreover, Schisandrin B notably inhibited the activation of mitogen activated protein kinase (MAPK) and nuclear factor-κB (NF-κB) pathways and scavenged ROS by activating nuclear factor E2 p45-related factor 2 (Nrf2) signaling. In conclusion, our study indicates that Schisandrin B is an effective approach to treat osteoporosis and other osteoclast-related diseases.